Efeitos de programas para promover o uso de estratégias de regulação emocional por parte de cuidadores familiares que assistem pessoas vivendo com demência: revisão sistemática da literatura - Yamada, Nicole Akemi (Universidade Federal de São Carlos, 2022)
Approximately two million Brazilians live with dementia, receiving the assistance of a family member who assumes the role of caregiver. In this context, interventions that focus on strengthening caregivers' skills to deal with the socio-emotional demands inherent to this role are important, but it is not clear which strategies are the most effective, especially in interactions with their relative with dementia. The objective of this study, therefore, was to analyze evidence about the effectiveness of different emotional regulation strategies used by or taught to family caregivers of people living with dementia. To address this objective, a systematic literature review was carried out to answer the following question: What emotional regulation strategies contribute to beneficial socioemotional outcomes among caregivers assisting family members who live with dementia? The research question was defined using the PICO strategy and the review was based on the PRISMA method. The bibliographic search was carried out in the following databases: SciELO, PsycNET, PubMed and Scopus, considering articles published in Spanish, English or Portuguese. The researchers conducted the review independently, using the Rayyan QCRI software package. The descriptors used were: (“emotional regulation” OR “emotion regulation” OR “self-regulation” OR “cognitive reappraisal” OR “emotional suppression”) AND ("caregiver*" OR "carer") AND ("dementia" OR "major cognitive disorder" OR "Alzheimer"), as well as their translations into English and Spanish. In total, 10 articles were selected for analysis, involving experimental studies to evaluate eight programs. Each program had a different focus, but taken collectively, participants worked on skills such as positive cognitive reevaluation, mindfulness, relaxation, and problem solving. A range of outcomes was evaluated, involving the intensity or frequency of negative feelings (such as depression, burden, and stress) and of positive feelings (such as positive affect and perceptions of wellbeing). The effects of all the programs were positive, but the size of the effects varied. Considering the studies that used a randomized clinical trial design, the Benefit-Finding (BF) program stood out, presenting a medium effect size for a decrease in depressive symptoms as well as for an increase in perceptions of positive aspects of care. As limitations, studies without a control group and with small sample sizes were included, and no Brazilian studies were found. In future studies, it will be important to adapta one of the programs for use in Brazil. Family caregivers of people living with dementia not only need help with situations taht lead to suffering, but also need activities and interactions that lead to satisfaction in their lives. The results encountered indicate that the education of emotion regulation strategies can contribute to these beneficial outcomes for this population.
Effects of programs to promote the use of emotion regulation strategies by family caregivers who assist people living with dementia: a systematic review of the literature
Keywords: Cuidadores; Idosos; Demência; Regulação emocional; Caregivers; Elderly; Dementia; Emotion regulation; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::RELACOES INTERPESSOAIS